2020
DOI: 10.1002/adfm.202002110
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Dimensional Lead‐Free Inorganic Perovskites for Resistive Switching with Ultralow Bias

Abstract: Abstract3D organic–inorganic and all‐inorganic lead halide perovskites have been intensively pursued for resistive switching memories in recent years. Unfortunately, instability and lead toxicity are two foremost challenges for their large‐scale commercial applications. Dimensional reduction and composition engineering are effective means to overcome these challenges. Herein, low‐dimensional inorganic lead‐free Cs3Bi2I9 and CsBi3I10 perovskite‐like films are exploited for resistive switching memory application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 96 publications
2
105
0
Order By: Relevance
“…Recently, our group reported excellent RS devices in 0D Cs 3 Bi 2 I 9 and 2D CsBi 3 I 10 perovskites with high on/off ratios (≈10 6 ) and a very low operation potential (≈0.12 V). [ 309 ] These findings further enrich the material library of all‐inorganic lead‐free perovskite RS devices.…”
Section: Rs Memories Based On Halide Perovskitesmentioning
confidence: 82%
“…Recently, our group reported excellent RS devices in 0D Cs 3 Bi 2 I 9 and 2D CsBi 3 I 10 perovskites with high on/off ratios (≈10 6 ) and a very low operation potential (≈0.12 V). [ 309 ] These findings further enrich the material library of all‐inorganic lead‐free perovskite RS devices.…”
Section: Rs Memories Based On Halide Perovskitesmentioning
confidence: 82%
“…Having said that, it is straightforward that different dimensionalities characterize Bi 3+ perovskites because of the different valences of bismuth and lead. XRD experiments showed that a 2D pattern characterizes the quite unusual CsBi 3 I 10 compound [78] with a bandgap of 1.77 eV. PV devices assembled using this harvester provide the best J sc of 3.4 mA cm −2 and V oc = 0.31 V for a CsI:BiI 3 precursor molar ratio 1:3.…”
Section: Bi and Other Halide Perovskitesmentioning
confidence: 93%
“…[ 17 ] Their intrinsic properties are basically derived from the 3D ABX 3 perovskites with the additional quantum confinement effect. [ 18 ] On the other hand, the intrinsic properties of molecular low‐dimensional metal halides are different from those of the 3D counterparts and controlled by discrete metal halide species, such as polyhedrons, layers, or wires, separated from each other by organic cations [17a,19] . Strictly speaking, most molecular low‐dimensional metal halides should not be called “perovskites” because they do not have an ABX 3 or equivalent stoichiometry comprising a cubic structure of corner‐sharing BX octahedra.…”
Section: Introductionmentioning
confidence: 99%